Can We Identify with a Nation Low in Morality? The Heavy Weight of (Im)Morality in International Comparison1. Issue 1 (19th September 2018) - Moscatelli, Silvia; Menegatti, Michela; Albarello, Flavia; Pratto, Felicia; Rubini, Monica
Abstract : Research has shown that the perceived morality of the ingroup is a primary source of group pride and ingroup identification. The present research examined whether this is true even when a group has a poor reputation for morality in terms of dishonesty and corruption, such as in the case of Italians. To address this issue, two studies analyzed the role of the three fundamental dimensions of social judgment—morality, competence, and sociability—in predicting Italians' identification with their nation when the salience of social comparison and the status of the comparison outgroup were varied. Findings showed that perceived morality predicted ingroup identification when participants did not engage in social comparison. Under salient social comparison, individuals based group identification on other dimensions: Perceived sociability was the main predictor of identification when respondents compared with a higher status outgroup (Germans; Study 1; N = 109), whereas perceived competence was the main predictor of identification when participants compared with a lower status outgroup (Romanians; Study 2; N = 121). Overall, findings showed compensation processes in social identification: When social comparison is salient, members of a low morality group base identification on the dimension which allows positive differentiation from the outgroup.